Genotypic difference of garlic (Allium sativum L.) cultivars for growth, bulb yield and yield related attributes at Tigray Province, Northern Ethiopia - Biratu, W.; Molla , B.; Abebe , H.; Gebremeskel , H. (International Journal of Horticultural Science, 2023)
The experiment was conducted at Ofla district from June to October of 2017 and 2018 cropping season to select high yielding and adaptable garlic cultivar(s). Six garlic cultivars namely Chefe, Tsedey, Holeta local, Kuriftu and Bora-4 and one Ofla Local were evaluated. The experiment was arranged in completely randomized block design (RCBD) with three replications. Different growth, phenology, yield and yield related data were collected. Leaf length, leaf width, bulb diameter and length were significantly (p